Inefficient Equilibrium Unemployment in a Duocentric Economy with Matching Frictions - Etienne Lehmann; Paola L. Montero Ledezma; Bruno Van der Linden (Institute for the Study of Labor (IZA), 2013)
This article examines unemployment disparities and efficiency in a densely populated economy with two job centers and workers distributed between them. We introduce commuting costs and search-matching frictions to deal with the spatial mismatch between workers and firms. In equilibrium, there exists a unique threshold location where job-seekers are indifferent between job centers. In a decentralized economy job-seekers do not internalize a composition externality they impose on all the unemployed. Their decisions over job-search are thus typically not optimal and hence the equilibrium unemployment rates are inefficient. We calibrate the model for Los Angeles and Chicago Metropolitan Statistical Areas. Simulations exercises suggest that changes in the workforce distribution have non-negligible effects on unemployment rates, wages and net output.
Keywords: J64; R13; R23; 330; spatial mismatch; commuting; urban unemployment; externality; United States